Efectos de un programa de entrenamiento en estrategias de aprendizaje - Martínez Arias, María del Rosario; Beltrán Llera, Jesús; Fernández Martín, María Poveda (Revista Española de Pedagogía, 2016)
This article shows a Training Program on Processing Strategies, following Beltran«s work on learning processes, strategies and techniques (1993,1996, 1997,1998). In this investigation the learning strategies (SO, SE, OE, SOE) were simultaneously applied to first-year secondary school students of social and natural sciences. The evaluation model was almost experimental, with a non-equivalent group control. The results were evaluated before and after the treatment. The data analysis was based on an ANCOVA, with the following variables: the treatment (experimental -learning strategies- and control) as inter-subject variable; the postest results as dependant variables and the pretest test variables, as covariant. The results of this research show that the treatments that included the three processing strategies (SOE) were more effective than those with only two simultaneous strategies (SE, SO, OE), both with regard to the control group of the several investigation variables and the two mentioned areas.
Keywords: Revista Española de Pedagogía